Store Atmosphere dan Kualitas Pelayanan Terhadap Loyalitas Konsumen Dimediasi Kepuasan Konsumen - Yulia Kartika Sam; Hanifah Husna; Adeliana Lubis; Risma Dewi Wahyu Mufti (Pusat Riset Manajemen Dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia, 2023)
This study aims to examine the effect of Store Atmosphere and Service Quality on Consumer Loyalty Mediated by Consumer Satisfaction at Locana Café. The sampling method used in this study was accidental sampling, with a total sample of 33 respondents. Data analysis technique using Structural Equation Modeling Part Least Square (SEM-PLS). The results showed that the quality of service to consumers has no effect, Service Quality has a significant effect on Customer Loyalty, Consumer Loyalty has a significant effect on Consumer Satisfaction, Store Atmosphere has a significant effect on Consumer Satisfaction, Store Atmosphere has no effect on Consumer Loyalty, Store Atmosphere has an effect on consumer loyalty through satisfaction consumers have no effect, service quality on consumer loyalty through customer satisfaction has a significant effect.